Pengembangan Pariwisata Berkelanjutan Melalui Peningkatan Fasilitas Pendukung Pada Desa Wisata Kampung Anyar, Banyuwangi, Jawa Timur - Kanom, Kanom; Sanjaya, Aditya Wiralatief; Rusmawan, Putu Ngurah (Alamtana: Jurnal Pengabdian Masyarakat UNW Mataram, 2025)
This Community Service Program aims to support sustainable tourism development through the improvement of supporting facilities in Kampung Anyar Tourism Village, Banyuwangi, East Java. The village possesses strong potential in Osing cultural and natural tourism but lacks adequate infrastructure. The program applied a Participatory Action Approach and Community-Based Tourism (CBT) principles by involving local communities in every stage of planning, implementation, and evaluation. Activities included the creation of a village tourism map, improvement of access to Ketegan Waterfall, installation of directional signs, construction of a tourism gate, and enhancement of natural attractions. The results indicate improved facility quality, visitor comfort, and community participation in destination management. The program also strengthened local identity and supported the achievement of Sustainable Development Goals (SDGs) 8, 11, and 12. This initiative serves as a replicable model for other tourism villages in implementing community-based sustainable tourism practices.